Generation and in vivo validation of an IL-12 fusion protein based on a novel anti-human FAP monoclonal antibody. Issue 9 (14th September 2022) - Nadal, Lisa; Peissert, Frederik; Elsayed, Abdullah; Weiss, Tobias; Look, Thomas; Weller, Michael; Piro, Geny; Carbone, Carmine; Tortora, Giampaolo; Matasci, Mattia; Favalli, Nicholas; Corbellari, Riccardo; et al.
Abstract : Background: In this study, we describe the generation of a fully human monoclonal antibody (named '7NP2') targeting human fibroblast activation protein (FAP), an antigen expressed in the microenvironment of different types of solid neoplasms. Methods: 7NP2 was isolated from a synthetic antibody phage display library and was improved by one round of mutagenesis-based affinity maturation. The tumor recognition properties of the antibody were validated by immunofluorescence procedures performed on cancer biopsies from human patients. A fusion protein consisting of the 7NP2 antibody linked to interleukin (IL)-12 was generated and the anticancer activity of the murine surrogate product (named mIL12-7NP2) was evaluated in mouse models. Furthermore, the safety of the fully human product (named IL12-7NP2) was evaluated in Cynomolgus monkeys. Results: Biodistribution analysis in tumor-bearing mice confirmed the ability of the product to selectively localize to solid tumors while sparing healthy organs. Encouraged by these results, therapy studies were conducted in vivo, showing a potent antitumor activity in immunocompetent and immunodeficient mouse models of cancer, both as single agent and in combination with immune checkpoint inhibitors. The fully human product was tolerated when administered to non-human primates. Conclusions: The results obtained in this work provided a rationale for future clinical translation activities using IL12-7NP2.